Stability of Organic Carbon Components in Shale: Implications for Carbon Cycle - Basu, Sudeshna; Verchovsky, Alexander B.; Bogush, Anna; Jones, Adrian P.; Jourdan, Anne-Lise (Frontiers in Earth Science, 2019)
Stability and mobility of organic matter in shale is significant from the perspective of carbon cycle. Shale can only be an effective sink provided that the organic carbon present is stable and immobile from the host sites and, not released easily during geological processes such as low pressure-temperature burial diagenesis and higher pressure-temperature subduction. To examine this, three Jurassic shale samples of known mineralogy and total organic carbon content, with dominantly continental source of organic matter, belonging to the Haynesville-Bossier Formation were combusted by incremental heating from temperature of 200 to 1400°C. The samples were analyzed for their carbon and nitrogen release profiles, bulk δ13C composition and C/N atomic ratio, based on which, at least four organic carbon components are identified associated with different minerals such as clay, carbonate, and silicate. They have different stability depending on their host sites and occurrences relative to the mineral phases and consequently, released at different temperature during combustion. The components identified are denoted as, C-1 (organic carbon occurring as free accumulates at the edge or mouth of pore spaces), C-2 (associated with clay minerals, adsorbed or as organomineral nanocomposites; with carbonate minerals, biomineralized and/or occluded), C-3(a) (occurring with silicate minerals, biomineralized and/or occluded) and C-3(b) (graphitized carbon). They show an increasing stability and decreasing mobility from C-1 to C-3(b). Based on the stability of the different OC components, shale is clearly an efficient sink for the long term C cycle as, except for C-1 which forms a very small fraction of the total and is released at temperature of ∼200°C, OC can be efficiently locked in shale surviving conditions of burial diagenesis and, subduction at fore arc regions in absence of infiltrating fluids. Under low fluid flux, C-3(b) can be efficiently retained as a refractory phase in the mantle when subducted. It is evident that the association and interaction of the organic matter with the different minerals play an important role in its retention in the shale.